Aspek Budaya Dalam Keistimewaan Tata Ruang Kota Yogyakarta (Cultural Aspect in the Speciality of Yogyakarta Urban Spatial Planning) - Suryanto .; Achmad Djunaedi; Sudaryono . (Journal of Regional and City Planning, 2015)
Dengan ditetapkannya budaya dan tata ruang kota sebagai penanda keistimewaan Yogyakarta dalam UU No. 13 tahun 2012 tentang Keistimewaan Yogyakarta, maka Yogyakarta merupakan kasus spesifik dalam Penataan Ruang, karena aspek Tata Ruang menjadi salah satu penanda Keistimewaannya. Apa yang istimewa. Apanya yang istimewa dang mengapa istimewa; apakah penanda (tata ruang kota), petanda (konsep budaya) atau makna/pesan dari hubungan antara petanda dengan penandanya yang tersirat dalam wujud tata ruang kota Yogya. Penelitian ini berupaya untuk mengenali dan memahami hubungan antara kebudayaan, tata kota dan keistimewaan Yogyakarta. Dari bukti-bukti empiris, kajian tentang kebudayan dan tata ruang kota memerlukan rentang waktu panjang, karena akan menyangkut data longitudinal (diakronik) dan lateral (sinkronik). Oleh karena itu studi ini perlu didudukkan dalam bingkai sejarah dan budaya, untuk membaca peristiwa sepanjang perkembangan kota Yogyakarta, dari HB I sampai HB IX. Kemudian untuk memahami makna kaitan antar penanda dan petanda sepanjang perjalanan perkembangan kota, maka digunakan metoda hermeneutika, khususnya Hermeneutik Paul Ricoeur. Dari hasil kajian terhadap obyek tata ruang kota yang dianggap istimewa, maka budaya yang mewujud dalam keistimewaan tata ruang kota Yogyakarta bisa dilihat dari komponen ruang kotanya maupun konfigurasi fungsi ruang kotanya. Kesimpulan penting dari penelitian ini adalah konsep budaya yang mewujud dalam tata ruang kota, yaitu monumental dan pertahanan, yang tidak ditemui di kota manapun di Indonesia. Kemudian dari sisi makna, terjadi perbedaan makna simbol-simbol tata ruang kota di era HB I dan HB IX.Kata kunci. Kebudayaan, tata ruang kota, budaya, Yogyakarta. Since Yogyakarta's culture and spatiality were proclaimed as special features of Yogyakarta as stated in Law No. 13, 2012 on the Special Region of Yogyakarta, Yogyakarta is recognized as a specific case in spatial planning, because its spatiality is one of the attributes that make it exceptional. Why is it exceptional and how is it exceptional? Because of its attributes (the space), its signature (the cultural concept), or the meaning/message of the relationship between its attributes and signature, which is implicitly manifested in Yogyakarta's spatiality? This research was aimed at identifying and explaining the relationship between the culture, spatial planning and special features of Yogyakarta. Research about culture and spatial planning based on empirical evidence takes a long time to complete, because it involves longitudinal and lateral (synchronic) data. Therefore, this study needed to utilize a historical and cultural framework in order to interpret events in the development of the city from the reign of Sultan Hamengkubuwono I to that of Hamengkubuwono IX. Additionally, in order to understand the meaning of the relationship between the attributes and the signature of the city throughout its development, the hermeneutic method of Paul Ricoeur was used. The results of this study of the spatial planning features of Yogyakarta that are considered exceptional reveal the culture that expresses itself in the components and functional configuration of Yogyakarta's urban space. An important finding from this research is that there is a cultural concept that manifests itself in the city's spatiality, i.e. monumental and defensive, which cannot be found in any other city in Indonesia. Moreover, it was found that there has been a change in the meaning of the city's spatial symbols from the era of Hamengkubuwono I to the era of Hamengkubuwono IX. Keywords. Culture, spatial planning, culture, Yogyakarta